Tanamera Coffee’s Service Scape in Relation to Employee Service Quality and Behavioral Intention with Overall Service Quality as Mediator - Soetanto, Tessa Vanina; Himawan, Leonardus Bryan; Sutikno, Daniel Viktor (Review of Management and Entrepreneurship, 2025)
Cafés have rapidly become a popular trend in Indonesia, evolving into an essential part of the local lifestyle. Due to the proliferation of café chains, owners are increasingly challenged to differentiate themselves by developing innovative concepts to attract customers and deliver value. Consequently, the concept of service scape has emerged as a crucial factor in securing a competitive edge. This study aims to examine the influence of service scape on service quality and customer behavioral intentions in the Indonesian market. A simple random sampling technique was used to distribute questionnaires to Tanamera Coffee patrons through social media platforms. A total of 111 valid responses were collected and analyzed using the partial least squares-structural equation modelling approach. The findings reveal that service scape directly affects employee service quality, overall service quality, and behavioral intentions. Moreover, employee service quality was found to positively influence overall service quality, which in turn had a significant impact on behavioral intentions. These insights underscore the pivotal role of service scape in enhancing customer value.